Денежное обращение Курской земли в золотоордынское время - Лебедев, В.П.; Зорин, А.В. (Степи Европы в эпоху средневековья, 2008)
The paper is devoted to the problem of monetary circulation on the territory of Kursk region in the Golden Horde time. The basis of the research is the numismatic material of this epoch which comes from hoards and single finds from the territory of modern Kursk province (Russia) and from some adjacent areas historically connected with this region. All 17 hoards of Juchi coins known on this territory so far as well as numismatic materials collected at some archaeological monuments of Kursk province (first of all, at the Ratskoie hillfort archaeological complex) have been analyzed.